The Role of Al Irsyad Al Islamiyyah to Development Islamic Education in Indonesia - Nursanti, Ririn (International Conference of Moslem Society, 2019)
Al Irsyad Al Islamiyyah as one of the Islamic organizations in Indonesia has a special nature, namely believers with Islamic aqeedah based on the texts of the Qur'an and Sunnah in providing services to the community, in the fields of education and teaching, preaching, economics and national-level socialism. The role of Al Irsyad Al Islamiyyah in education in Indonesia is very influential and gives its own style in the development of education in Indonesia, which is having a commitment to develop students for the realization of a civilized society and Islamic character, and able to benefit the people of Indonesia. The education principle of Al Irsyad Al Islamiyyah is to foster a scientific culture among Muslims, with reference to the Qur'an and Sunnah, so that it will form a mindset that is characterized by Islam properly and correctly. This concentration on the modernization of education has made Al Irsyad Al Islamiyyah have played many roles in the advancement of education in Indonesia. The development of Islamic education carried out by Al Irsyad Al Islamiyyah is under the responsibility of the Education and Teaching Council through the program; 1) publishing an education quality management system, 2) publishing curriculum and textbooks on Islamic Education, Al Qur'an and Arabic subjects, 3) conducting school management assistance in each branch, 4) holding training / workshops to improve school management competencies and teachers, and 5) measuring the development of Al Irsyad Al Islamiyyah schools.